Comparative industrial relations : an introduction to cross-national perspectives - Bean, R. 1938- (International Thomson Business Press, 1996)
Introduction. Trade unions. Employers and managements. Collective bargaining. The role of state. Industrial conflict and strikes. Workers' participation in decision-making...